Investor Behavior In Islamic Capital Markets: Study On Muslim Students - Irton Irton; Salihah Khairawati; Mu’tashim Billah Murtadlo (Jurnal Manajemen Bisnis Performa, 2021)
ABSTRACTThe purpose of this research is to know the behavior of investors towards Islamic capital market. The research was conducted on several Muslim student respondents from several universities in Yogyakarta who invested in sharia capital markets. The type of data in this study is primary data obtained through in-depth interviews. The results showed that there are two investor characters among students namely risk seeker or risk taker and risk-averse. Respondents realized that investing in the capital market has potential benefits as well as potential risks. For investors, risk seeker has high confidence and optimism when making investment decisions, while risk-averse tends to be cautious and a lot of consideration when making investment decisions. In general, sharia capital market investors who are the majority of students have a good belief in the wisdom of stocks traded in sharia capital markets. They believe in the fatwa of scholars, the role of the DSN, and the role of capital market supervisory bodies. They are mostly also looking for information about sharia capital market sharia through books, capital market socialization, IDX web. In terms of transaction mechanisms in the sharia capital market only a small part still doubts its validity due to issue factors, lack of understanding of islamic capital market the correctness factor of the company's financial performance, and the ups and downs of the share price.Keywords: investor behavior, investment decisions, sharia capital market ABSTRAK Tujuan penelitian ini adalah untuk mengetahui perilaku investor terhadap pasar modal syariah. Penelitian dilakukan terhadap sejumlah responden mahasiswa muslim dari beberapa perguruan tinggi di Yogyakarta yang melakukan investasi di pasar modal syariah. Jenis data dalam penelitian ini adalah data primer yang diperoleh melalui wawancara Hasil penelitian menunjukkan bahwa terdapat dua karakter investor di kalangan mahasiswa yakni risk seeker atau risk taker dan risk averse. Responden menyadari bahwa investasi di pasar modal memiliki potensi untung dan juga potensi resiko. Bagi investor risk seeker memiliki rasa percaya diri yang tinggi dan optimis ketika mengambil keputusan investasi, sedangkan risk averse cenderung berhati-hati dan banyak pertimbangan ketika mengambil keputusan investasi. Secara umum investor pasar modal syariah yang merupakan mahasiswa mayoritas memiliki keyakinan yang baik mengenai kesyariahan saham-saham yang diperdagangkan di pasar modal syariah. Mereka percaya terhadap fatwa ulama, peranan DSN dan peranan badan pengawas pasar modal. Mereka sebagian besar juga mencari informasi tentang kesyariahan pasar modal syariah melalui buku, sosialisasi pasar modal, web IDX. Pada aspek mekanisme transaski pada pasar modal syariah hanya sebagian kecil yang masih meragukan kesyariahannya, karena faktor isu dan kurangnya pemahaman, faktor adanya unsur ketidakpastian naik turunnya harga saham.Kata kunci : perilaku investor, keputusan investasi, pasar modal syariah